The Revenge of the Shadow King - Benz, Derek; Lewis, J. S. (Jon S.). (New York : Orchard Books, 2006)
When Max Sumner and three friends play a magical card game called Round Table, they realize that it is up to them to prevent the wicked creatures of the cards from destroying their town, indeed, their world.
"A Grey Griffins book."